1978
DOI: 10.4141/cjps78-024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mineral Nutrition on Cooking Quality of Lentils

Abstract: of mineral nutrition on cooking quality of lentils. Can. J. plant sci. 5g: 165-168. A pot experiment was conducted on lentils to study the influence of major and trace elements on the-cooking quality of a hard cooliing lentil. cooking

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…Such differences in cooking time among lentil varieties have also been reported by other researchers (Bhatty et al, 1984;Bhatty, 1988). Wassimi et al (1978) and Bhatty et al (1984) have attributed these differences mainly to the variety (genotypes) influence but with a minor contribution to soil fertility. However the differences in cooking time between the different soil types in this experiment were small and not significant in the majority of the cases for the varieties ÔSamosÕ and ÔDimitraÕ, but, the differences were large and statistically significant in the majority of the cases for the varieties ÔArachovaÕ and ÔPelasgiaÕ (Figs 1 and 2).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Such differences in cooking time among lentil varieties have also been reported by other researchers (Bhatty et al, 1984;Bhatty, 1988). Wassimi et al (1978) and Bhatty et al (1984) have attributed these differences mainly to the variety (genotypes) influence but with a minor contribution to soil fertility. However the differences in cooking time between the different soil types in this experiment were small and not significant in the majority of the cases for the varieties ÔSamosÕ and ÔDimitraÕ, but, the differences were large and statistically significant in the majority of the cases for the varieties ÔArachovaÕ and ÔPelasgiaÕ (Figs 1 and 2).…”
Section: Resultssupporting
confidence: 80%
“…This soil influence, although important, has been studied very little. Different cooking times were found in lentil when cultivated in different locations and this was attributed to different soil fertility (Wassimi et al, 1978;Bhatty et al, 1983;Bhatty et al, 1984). In chickpeas the Ôlong cooking timeÕ attribute was more strongly influenced by different soil types than Ôshort cooking timeÕ varieties (Iliadis et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…. The hard-tocook phenomenon is common in grain legumes and has also been reported for lentils (Wassimi et al, 1978). Bhatty (1990) reported that in field-grown lentils, the hard-tocook phenomenon may stem solely from cotyledons and not the seed coat, which can only reduce water uptake during cooking.…”
mentioning
confidence: 83%
“…The hard-tocook phenomenon is common in grain legumes and has also been reported for lentils (Wassimi et al, 1978). The hard-tocook phenomenon is common in grain legumes and has also been reported for lentils (Wassimi et al, 1978).…”
mentioning
confidence: 84%
“…A great deal of effort has been spent on studying cooking time and the factors affecting it in pulses (e.g. Halstead and Gfeller, 1964;Morris et al, 1950;Quenzer et al, 1978;Wassimi et at., 1978;Youssef, 1978;Shrivasankar et al, 1974). To some extent, this type of work has been inhibited by the lack of an objective method for the determination of cooking time.…”
Section: Introductionmentioning
confidence: 99%